2021
DOI: 10.31703/gmcr.2021(vi-i).01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horror Movies on Psychological Health of Youth

Abstract: The current study is an explanatory study on the effects of watching horror movies on the psychological health of teenagers in the city area of Faisalabad. Researchers tried to explain the mental health and psychological problems like phobias, nightmares, sleep disorder, harsh behavior etc., in teenagers and their preferences of movies watching. The study explains that the majority of teenagers are used to watching movies, and they prefer Horror and Action movies via the internet, and these movies are affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In this study, Irem included other previous research conducted by (Baird, 2000). Research by Irem et al found the result that watching horror movies apparently can make someone shrouded in fear and discomfort (Sultana et al, 2021). Then, 31.7% feel better when watching a horror movie, the attraction to curiosity, adrenaline rushes, and a sense of alertness favored some people.…”
Section: Resultsmentioning
confidence: 88%
“…In this study, Irem included other previous research conducted by (Baird, 2000). Research by Irem et al found the result that watching horror movies apparently can make someone shrouded in fear and discomfort (Sultana et al, 2021). Then, 31.7% feel better when watching a horror movie, the attraction to curiosity, adrenaline rushes, and a sense of alertness favored some people.…”
Section: Resultsmentioning
confidence: 88%
“…Participants were enquired and assessed for clinical and subclinical conditions that could bias their performance during the experiment (see Sultana et al, 2021). They should not have a current or previous DSM-5 Axis I (clinical disorders) or II (personality disorders) diagnosis (American Psychiatric Association, 2013) or a diagnosis for dyslexia; self-report (Y/N).…”
Section: Stage One: Stimuli Preselectionmentioning
confidence: 99%
“…Це вказує на те, що люди, які дивляться фільми жахів, розвивають здатність справлятися зі стресовими ситуаціями, а також мінімізувати власне занепокоєння [20]. На думку психологів, фільми жахів здійснюють десенсибілізуючий ефект, який є досить корисним для подолання страху та фобій [17].…”
unclassified
“…Перегляд комедій може забезпечити відчуття психологічної безпеки, дистанціювати від складних ситуацій, підкреслити той факт, що всі люди, стикаючись із повсякденними складнощами, схильні знаходити вихід. Використання в комедійних фільмах чорного гумору на такі теми, як смерть, хвороба, депресія або трагедія, допомагає людині інакше ставитися до проблем [15].…”
unclassified